2001
DOI: 10.1103/physreve.63.046211
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization as adjustment of information rates: Detection from bivariate time series

Abstract: An information-theoretic approach for studying synchronization phenomena in experimental bivariate time series is presented. "Coarse-grained" information rates are introduced and their ability to indicate generalized synchronization as well as to establish a "direction of information flow" between coupled systems, i.e., to discern the driving from the driven (response) system, is demonstrated using numerically generated time series from unidirectionally coupled chaotic systems. The method introduced is then ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
246
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(260 citation statements)
references
References 17 publications
3
246
0
4
Order By: Relevance
“…Timedelayed mutual information quantifies the co-dependence between variables by considering shared previous information content as a function of time (Nichols et al 2005;Palus et al 2001;Vastano and Harry 1988). Here we analyse the delayed mutual information (DMI) estimated from a large multivariate neurobiological data set obtained by Angarita-Jaimes et al (2012), Kondoh et al (1995), Newland and Kondoh (1997a,b) and Vidal-Gadea et al (2010) from a neural network that produces and controls movements of the hind leg of an insect, the desert locust.…”
Section: Introductionmentioning
confidence: 99%
“…Timedelayed mutual information quantifies the co-dependence between variables by considering shared previous information content as a function of time (Nichols et al 2005;Palus et al 2001;Vastano and Harry 1988). Here we analyse the delayed mutual information (DMI) estimated from a large multivariate neurobiological data set obtained by Angarita-Jaimes et al (2012), Kondoh et al (1995), Newland and Kondoh (1997a,b) and Vidal-Gadea et al (2010) from a neural network that produces and controls movements of the hind leg of an insect, the desert locust.…”
Section: Introductionmentioning
confidence: 99%
“…According to this concept, Porta et al [8] exploited the definition of conditional entropy [9] to measure causality in bivariate systems as the amount of information carried by one process when the past of the * Author to whom correspondence should be addressed: luca.faes@unitn.it other process is known. Further developing this idea through independent approaches, Schreiber [10] and Palus et al [11] defined the concepts of transfer entropy and conditional mutual information, which have been shown to be equivalent later on [12]. These measures allow us to quantify the amount of information exchanged between two systems separately for both directions and, when desired, conditional to common signals.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of causality based on information transfer is framed in different terms with respect to the Granger approach, the first involving the concept of uncertainty and the second the concept of predictability. Nevertheless, the relation between transfer entropy and Granger causality is known [11,13], and analytical equivalence has been very recently demonstrated [14], bridging information-theoretic approaches to the classical predictability-based approaches for the evaluation of causality.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same method one could equally well analyse the combinatorial frequencies responsible for the influence of cardiac on the respiratory system. In fact, using newly developed algorithms for analysis of the direction of coupling (Schreiber 2000, Rosenblum and Pikovsky 2001, Rosenblum et al 2002, Paluš et al 2001, it has already been shown (Stefanovska 2002, Paluš and) that the two systems are bidirectionally coupled. The effect of respiratory system is, however, dominant (i.e.…”
Section: Unidirectional or Bidirectional Couplingmentioning
confidence: 99%
“…The interactions can be detected by analysis of recorded time series, and their strength and direction can also be determined (Schreiber 2000, Rosenblum and Pikovsky 2001, Paluš et al 2001, Rosenblum et al 2002, Paluš and Stefanovska 2003. The next logical step in studying interactions among the coupled oscillators must be to determine the nature of the couplings from the time series.…”
Section: Introductionmentioning
confidence: 99%